The Role of Instagram Ads in Increasing the Attraction of Healthy Bread Products - Halim, Adam; Theofillus, Michael; Sianipar, Rosianna; Juliana, Juliana (Sean Institute, 2025)
The growing trend of healthy living among urban communities has driven increased interest in healthy food products, including healthy bread. Healthy bread refers to bread formulated with nutritious ingredients such as whole grains, seeds, or low-sugar flour, and is typically low in fat and high in fiber. As consumer awareness of balanced diets rises, social media platforms like Instagram have become key tools for promoting such products, particularly among younger audiences. This study aims to analyze the influence of Instagram advertising, exposure frequency, and consumer engagement on the purchase decision of healthy bread products. This research employs a quantitative method with a descriptive approach. The sampling technique used is purposive sampling with 171 respondents who have seen healthy bread advertisements on Instagram. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. The results indicate that all three independent variables—Instagram advertising, exposure frequency, and consumer engagement—have a positive and significant effect on purchase decision. These findings highlight the effectiveness of consistent ad exposure and active consumer interaction with promotional content in increasing the likelihood of purchasing healthy food products such as healthy bread.